KEWAJIBAN DAN IMPLEMENTASI UNDANG-UNDANG NO 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN TERHADAP PENGENDARA MOTOR DIBAWAH UMUR DI KABUPATEN NGAWI - Grahita, Agasta Ardhya; Sidarta, Dudik Djaja; Ayuningtyas, Fitria; Paramitha, Vallencia Nandya (Gapenas Publisher, 2025)
This thesis is entitled “Obligations and Implementation of Law Number 22 of 2009 concerning Road Traffic and Transportation for Underage Motorcyclists in Ngawi Regency”. Law Number 22 of 2009 on Road Traffic and Transportation strictly regulates traffic safety, including prohibiting minors from driving motor vehicles. This study uses a normative juridical method with a legislative approach, supplemented by empirical data obtained through interviews with students, parents, school officials, and police officers. The findings reveal that although the legal regulations are clearly structured, their implementation in the field has not been optimal. Low public awareness of the law, lack of parental supervision, limited access to public transportation, and weak socialization are the main obstacles. The lack of synergy among stakeholders also exacerbates the situation. Therefore, it is necessary to strengthen legal socialization, consistent enforcement of regulations, provision of adequate transportation, and cross-sector cooperation to improve the effectiveness of the implementation of these regulations in everyday life